Peran Guru Dalam Menerapkan Karakter Tanggung Jawab Siswa Di SDN 1 Jeumpet Kabupaten Aceh Besar - Annisa Rahmania Farcha; Aida Fitri; intan Safiah (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2023)
This study plans to decide the educator's part in carrying out the personality of understudy liability at SDN 1 Jeumpet. This study utilized elucidating subjective technique. In dissecting the information utilizing information decrease, information show, and reaching determinations. The consequence of this review is that the educator plays completed his part in the homeroom as a learning planner, guide, and evaluator. Nonetheless, there are numerous understudies who have not completed their obligations appropriately in that frame of mind, as the errands that ought to have been done have not been completed as expected, then the absence of familiarity with understudies in their obligations, like not doing schoolwork, littering, and not doing class pickets. The finish of this study is that the instructor has applied the personality of obligation to understudies to the greatest. The job of educators as teachers should be engaged with the growing experience, conversation, and requiring drives as a work to fabricate character schooling. Educators are likewise dependable as models who have virtues and make the most of chances to impact their understudies. Hence, it is trusted that schools ought to continuously apply different characters other than liability, consistently convey the person advancement of understudies to their folks, and instructors should be good examples for their understudies in light of the fact that the educator is the second parent for understudies.